2020
DOI: 10.35799/vivabio.3.1.2021.31380
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan dan Pendampingan UMKM di Desa Gajahrejo dalam Pembuatan Desain Kemasan Inovatif Oleh-Oleh Khas Malang Untuk Meningkatkan Daya Saing Produk

Abstract: Salah satu masalah yang dihadapi oleh UMKM di Malang adalah menciptakan kemasan yang menarik khususnya produk makanan dan oleh-oleh khas Malang. Padahal peran kemasan sangat penting karena menciptakan kesan pertama bahkan sebelum produk dikonsumsi. Kemasan telah mendukung penciptaan nilai tambah bagi sebuah produk dari segi bentuk, warna, hingga grafisnya. Kemasan juga berfungsi dalam membangun indentitas sebuah produk. Indentitas yang tidak konsisten dapat menyebabkan konsumen kesulitan dalam mengenal produk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Standard financial reports are essential in this case, helping MSMEs identify financial positions and track income, expenses, assets, debts and other aspects (Fauzi, 2020;Emilda et al, 2022). Meanwhile, training on product marketing is expected to improve the ability of Micro, Small and Medium Enterprises (MSMEs) products in Dukun Gresik to compete with other products and build a strong brand identity to attract customers to research conducted by Ariyani et al (2022) and Kurniawan et al (2020) who revealed that packaging design can influence the branding of MSMEs and increase the selling power of their products. Digital marketing can also increase sales of MSME products because it can reach more parties (Fahdia, 2022).…”
Section: Results and Discussion The Role Of Sharia Cooperatives As Id...mentioning
confidence: 99%
“…Standard financial reports are essential in this case, helping MSMEs identify financial positions and track income, expenses, assets, debts and other aspects (Fauzi, 2020;Emilda et al, 2022). Meanwhile, training on product marketing is expected to improve the ability of Micro, Small and Medium Enterprises (MSMEs) products in Dukun Gresik to compete with other products and build a strong brand identity to attract customers to research conducted by Ariyani et al (2022) and Kurniawan et al (2020) who revealed that packaging design can influence the branding of MSMEs and increase the selling power of their products. Digital marketing can also increase sales of MSME products because it can reach more parties (Fahdia, 2022).…”
Section: Results and Discussion The Role Of Sharia Cooperatives As Id...mentioning
confidence: 99%
“…Dalam sebuah kemasan terdapat tiga unsur utama yaitu kemasan itu sendiri, merek dan informasi produk. Desain kemasan memiliki peran penting, karena kemasan inilah yang akan pertama kali dilihat oleh konsumen dan memberikan kesan pertama (Kurniawan, Anugrahani, Prasasti, & Fitri, 2021). Pepatah "don't judge a book by its cover" kurang tepat untuk diterapkan pada sebuah produk dimana persaingannya sangat ketat.…”
Section: Pengenalan Dan Penentuan Desain Kemasanunclassified
“…Packaging design actually strengthens the perception of a product's quality. The appearance and aesthetics of the packaging are actually very important in building a product brand (Kurniawan et al, 2021). Apart from packaging, the visual attraction for typical tourist souvenirs is how to display them on shelves or booths, it is also related to visual merchandising.…”
Section: Introductionmentioning
confidence: 99%